DEVELOPMENT OF SMART-LAB STEAM INTEGRATED WITH AUGMENTED REALITY AND ADAPTIVE LEARNING SYSTEM FOR STRENGTHENING CHEMISTRY TEACHERS’ PROFESSIONAL COMPETENCIES: A LITERATURE REVIEW - Khaerunnisa Khaerunnisa; Eda Lolo Allo; Dewiyanti Fadly (University of Bengkulu, 2026)
This innovation aims to design the concept of SMART-LAB STEAM integrated with Augmented Reality (AR) technology and an Adaptive Learning System (ALS) as a novel advancement beyond previous digital laboratory models. Unlike conventional Hybrid Digital Laboratories that merely combine physical and virtual labs, the model proposed in this literature study integrates AR technology for immersive visualization of chemical reactions and an AI-based adaptive system capable of tailoring learning content to each teacher’s individual competency profile. The method employed is a systematic literature review of 35 scientific articles from reputable databases (Scopus, Google Scholar, ERIC) published between 2019–2024. The results indicate that AR integration in virtual laboratories significantly enhances chemistry concept comprehension, while ALS has proven effective in identifying teacher competency gaps and providing personalized learning pathways. The resulting SMART-LAB STEAM model comprises three main components: (1) an AR-Chemistry module for interactive molecular visualization, (2) an AI-based adaptive competency diagnostic system, and (3) cross-disciplinary STEAM projects contextualized to South Sulawesi’s local setting. This innovation is projected to strengthen the professional competencies of chemistry teachers, particularly in technology-based subject mastery and innovative pedagogy.